Estimation of the active and functional components of basil seed gum extract and their use in whole (NTU Journal of Agriculture and Veterinary Science, 2023)
The study aimed to extract the gum of basil seeds and estimate its content of sugars and phenolic and active compounds, and then study the effect of its addition on the chemical and physical properties of curd made from whole milk (3 fat). gum on ( D - Xylose, L-Arabinose, D-Glucose, D - Galactose, and D-Manose )by percentages of 10.75, 10.71, 10.03, 7.56, and 2.82%, respectively. The results of the infrared spectrum analysis (FTIR) of the basil seed gum showed that it contained hydroxyl groups OH, the amine group - carbonyl groups C-HR and aldehyde groups CO, while the results of the diagnosis of phenolic compounds showed that the gum of basil seeds contains compounds Catechine, Chorogenic acid, Rutin, Gallic acid, Quercetin, and Ferulic acid Apigenin with percentages of 23.22, 18.24, 18.22, 17.98, 16.5, 13.04 and 11.42%, respectively, and the addition of basil seed gum to the curd improved its properties as it decreased the pH values, moisture and whey separation while there was an increase in viscosity3 introductory words: basil seed gum, phenolic compounds, curd, monosaccharides in basil seed gum, FTIR-Spectro scopy.